VENTIlatory strategies for patients with severe traumatic brain injury in the LOw-and Middle-Income CountrieS. The VENTILOMICS survey - Hemanshu, Prabhakar; Charu, Mahajan; Indu, Kapoor; Gentle S., Shrestha; Edoardo, Picetti; Chiara, Robba; Marcus J., Schultz; Mani, Kalaivani; Samuel Ern Hung, Tsan (Brazilian Intensive Care Medicine Association (AMIB), 2025)
Objective: To revisit the VENTIlatory Strategies for Patients with Severe Traumatic Brain Injury (VENTILO) survey, focusing on ventilatory management practices among healthcare professionals in low- and middle-income countries. Methodology: A cross-sectional on-line survey, VENTIlatory strategies for patients with severe traumatic brain injury in the LOw- and Middle-Income CountrieS (VENTILOMICS), was conducted using the original VENTILO survey questionnaire, developed following a review of literature on respiratory management in traumatic brain injury patients, captured demographics of participants, type of hospital/specialty and available neuromonitoring tools; protocols for mechanical ventilation and weaning, and respiratory management strategies. Descriptive statistics were computed for all study variables. We analyzed data based on the economic status of the low- and middle-income countries. Results: There were 204 respondents from 28 low- and middle-income countries. Our results indicate that 55 - 70% of respondents recommend tidal volumes of 6 - 8mL/kg for patients with high or medium partial pressure of arterial oxygen/inspired fraction of oxygen, while tidal volumes of 4 - 6mL/kg is preferred for those with low partial pressure of arterial oxygen/inspired fraction of oxygen ratios. For patients with intracranial hypertension, lower positive end-expiratory pressure levels were utilized. Conclusion: The findings suggest a consistent approach to lung-protective ventilation across low-and middle-income countries, with notable variations influenced by local resources and economic status. This study highlights the necessity for tailored research and guidelines to address the specific challenges faced in traumatic brain injury management within low-and middle-income countries.